Kegiatan Initial untuk Meningkatkan Kemandirian Belajar: Studi Kasus di Fakultas Keguruan dan Ilmu Pendidikan - Khulaifiyah (Medan Resource Center, 2022)
The study aims to explore how lecturers enhance learners’ autonomous learning. Autonomous learning is a process to be aware of taking control of learning. This study used a case study and a content analysis in the qualitative research. A qualitative approach is chosen as research design with the help of Nvivo 12 Apps since interviews become the main instrument. Some interview items questioned how lecturers help learners comprehend the material, determine their personal goals, finding out supporting resources. The study reveals that the lecturer activities as the initial activities were giving the material explanation, giving information about the course outline, giving assignments, giving what students need, giving motivation, having a negotiation, having references of material, sharing experiences, checking students’ comprehension by reviewing, giving question and answer time. Yet, giving assignments individually or in collaboration, projects or incidental test becomes a proposed activity in the initial process to enhance learners’ autonomous